RANCANG WEB PADA TOMART COMPUTER - Novri Adhiatma (JURNAL AKADEMIKA)
The developing of business that make great strides at this time, made information as a thing that has important role in supporting the way of operations to achieve the desired goal of company. Tomart computer is one of business that is engaged in commercial activities, that is selling computer. At tomart computer sales is doing lineal, that is the buyers come to the store to see or buy the desired item directly.With the development of technology information that very quickly, then designed a sales system web-based that can be accessed by candidate buyers and web visitors, so they can know information about the goods that offered in detail and buy it directly.